2017
DOI: 10.1007/s11010-017-3102-1
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-200a induce cell apoptosis in renal cell carcinoma by directly targeting SIRT1

Abstract: Accumulating evidence indicates that microRNAs are implicated in tumor initiation and progression through negatively regulating oncogenes or tumor suppressor genes. In the present study, we report that the expression of miR-200a was significantly lower in renal cell carcinoma (RCC) specimens and RCC cell lines. Restoration of miR-200a suppressed cell growth, arrested cell cycle progression, and promoted cell apoptosis in RCC cell lines. We next used qRT-PCR array technology to identify Sirtuin 1 (SIRT1) as one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In the past decades, the roles of cellular miRNA abnormalities in the pathogenesis of most human cancers have been intensely investigated. [25][26][27] Furthermore, the miR-200a-3p/ CBL pathway has not been explored in RCC. In the current study, we focused on understanding the pathological roles of miR-200a-3p in RCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, the roles of cellular miRNA abnormalities in the pathogenesis of most human cancers have been intensely investigated. [25][26][27] Furthermore, the miR-200a-3p/ CBL pathway has not been explored in RCC. In the current study, we focused on understanding the pathological roles of miR-200a-3p in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] To further uncover the underlying mechanisms of the suppression of RCC cell growth and migration mediated by miR-200a-3p, we searched for miRNA targets and identified CBL as a novel target of miR-200a-3p. [26][27][28] To further uncover the underlying mechanisms of the suppression of RCC cell growth and migration mediated by miR-200a-3p, we searched for miRNA targets and identified CBL as a novel target of miR-200a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…transcription factors and transcriptional coregulators as well as miRNAs [9,15,18,24,39]. Our previous studies have demonstrated that the GMC apoptosis evoked by sublytic C5b-9 in rat Thy-1N is associated with the upregulation of some specific transcription factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…IRF-1 acetylation by p300) [15,18,20]. Recently, several experiments have revealed that miR-200a and miR-1469 are involved in regulating cell apoptosis [24,40]. Given that miRNAs can affect target gene expression by binding to the complementary sites of mRNAs 3` UTR causing mRNA degradation or translation inhibition [21,23], and many researchers have found that miRNAs such as miR-148b, miR-29c and miR-29b are important regulators of viral infection, cancer or diabetes including MsPGN [24-28, 39, 41], the effects of miRNAs on the GMC apoptosis mediated by sublytic C5b-9 in Thy-1N rats and the underlying mechanism needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation